ANALISA TINGKAT KEBISINGAN PADA SEKOLAH DASAR NEGERI DI KECAMATAN MEDAN BARU DAN KECAMATAN MEDAN PETISAH TAHUN 2013 - Winda Lidia Wati Sihite; Ir. Indra Chahaya M.Si; dr. Surya Dharma,MPH (Lingkungan dan Kesehatan Kerja, 2014)
The Analysis of Noise Level in Elementary School at Medan Baru and Medan Petisah Subdistrict in 2013. Noise is an element of the physical environment that can interfere with human health and the environment because of convenience distraction in daily activities. Activities in urban transportation is one thing that has high potential as a source of noise. To avoid noise impact stipulated limit their level of noise that can be accepted by hearing, for a school environment which is equal to 55 dB (A).This study is an descriptive survey study, that aims to determine the noise level classrooms and libraries, highway noise levels, the distance of school to the highway, the physical condition of the public elementary school at the Medan Baru and Medan Petisah Sub District in 2013. Population elementary school in Medan Baru and Medan Petisah Sub District entirely sampled is 23 schools. Data collected by direct measurements of noise levels by using a Sound Level Meter and direct observation using the observation sheet about the physical condition of school buildings. Measurement results and observations are presented descriptively in tabular form. The results showed that the noise level around the class room and library room 23 Public Elementary School is 55,9-71,5 dBA, no qualified health determined that all of > 55 dB (A). For the physical condition of the building, all the school has met the requirements of the noise, but none of the schools that have control of noise from both outside and inside the room. According to the results of the research, it is suggested should be made efforts to reduce the noise level by installing noise barriers in school room, the use green belt along the highway, planting trees and creating a barrier or obstacle (fance) that not disconnected, solid, and not hollow between schools and roads highway. For the near future, the noise can be reduced by covering the walls of the classroom with thick curtains and close the door during the learning procces.Keywords: Noise levels, Schools, Highways, Distance, Physical Condition